2016
DOI: 10.1002/dvdy.24389
|View full text |Cite
|
Sign up to set email alerts
|

Syndactyly in a novel Fras1rdf mutant results from interruption of signals for interdigital apoptosis

Abstract: Fras1 encodes an extracellular matrix protein that is critical for the establishment of the epidermal basement membrane during gestation. In humans, mutations in FRAS1 cause Fraser Syndrome (FS), a pleiotropic condition with many clinical presentations such as limb, eye, kidney, and craniofacial deformations. Many of these defects are mimicked by loss of Fras1 in mice, and are preceded by the formation of epidermal blisters in utero. In this study, we identified a novel ENU-derived rounded foot (rdf) mouse mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…FRAS1 is similar in function to collagen VII and plays a significant role in epithelial–stromal adhesion during mouse embryogenesis . Patients with Fraser syndrome, a genetic disorder, present with congenital malformations such as cryptophthalmos, syndactylism and reno‐urinary anomalies caused by FRAS1 mutations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FRAS1 is similar in function to collagen VII and plays a significant role in epithelial–stromal adhesion during mouse embryogenesis . Patients with Fraser syndrome, a genetic disorder, present with congenital malformations such as cryptophthalmos, syndactylism and reno‐urinary anomalies caused by FRAS1 mutations …”
Section: Discussionmentioning
confidence: 99%
“…19 Patients with Fraser syndrome, a genetic disorder, present with congenital malformations such as cryptophthalmos, syndactylism and reno-urinary anomalies caused by FRAS1 mutations. 20,21 FRAS1 is associated with cancers. For example, a FRAS1-knockdown in a lung cancer cell line inactivates the FAK pathway and suppresses tumor invasion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of consanguinity in families with FS is estimated reaching 15% to 30% 2,4,7,27 . This syndrome seems to be related to a failure of the apoptosis program and to the formation of large blisters during embryonic development due to defects in epidermal adhesion (disruption of the epithelial-mesenchymal interactions) [28][29][30] . Indeed, in embryos, the Fraser complex (FC) mediates epithelial-connective tissue interactions.…”
Section: Physiopathology and Geneticsmentioning
confidence: 99%
“…Mutations in FRAS1 in humans cause Fraser syndrome (OMIM 219000) with eye, kidney, and craniofacial defects [48]. Hines et al [49] identified a novel ENU-derived rounded foot (rdf) mouse mutant with hindlimb cutaneous syndactyly caused by loss-of-function nonsense allele of Fras1 . The primary defect in these animals was the decreased Msx2 expression [49].…”
Section: The Unified Pathway Of Pathogenesis Of Syndactylymentioning
confidence: 99%
“…Hines et al [49] identified a novel ENU-derived rounded foot (rdf) mouse mutant with hindlimb cutaneous syndactyly caused by loss-of-function nonsense allele of Fras1 . The primary defect in these animals was the decreased Msx2 expression [49]. As mentioned above, deficiency of Msx1/2 is associated with extended Fgf activity in the AER [47].…”
Section: The Unified Pathway Of Pathogenesis Of Syndactylymentioning
confidence: 99%